The Impact of ERP System Integration, User Training, and Management Support on Operational Efficiency in Mobile Coffee Businesses in Major Cities of Indonesia - Haryono, Haryono; Epriliati, Indah; Muchid, Mochammad; Prasetyo, Eko (West Science Information System and Technology, 2024)
This study investigates the impact of Enterprise Resource Planning (ERP) system integration, user training, and management support on operational efficiency in mobile coffee businesses across major cities in Indonesia. A quantitative approach was adopted, involving 65 business owners and managers who provided insights into their ERP adoption processes. Data were collected using structured questionnaires with a Likert scale of 1 to 5 and analyzed using SPSS version 26. The findings revealed that ERP system integration, user training, and management support each significantly and positively impact operational efficiency. ERP system integration and management support were the strongest predictors of improved operational performance. These results suggest mobile coffee businesses can optimize their operations by leveraging ERP systems, enhancing employee training, and ensuring continuous management support. The study provides valuable recommendations for business owners seeking to enhance their operational strategies in a competitive market.